Collisional electrochemistry of laser-ablated gold nanoparticles by electrocatalytic oxidation of glucose - Liu, Y.; Austen, B.; Cornwell, T.; Tilbury, R.; Buntine, Mark; O'Mullane, A.; Arrigan, Damien (Elsevier Inc., 2017)
We report the electrochemistry of gold nanoparticles (AuNPs), prepared by Laser Ablation Synthesis in Solution (LASiS), via the electrocatalytic oxidation of glucose upon single nanoparticle collisions at inert microelectrodes. Spherical AuNPs with diameters in the range 20–30 nm, as determined by transmission electron microscopy, were synthesized by LASiS of a gold plate immersed in water. Nanoparticle collisions were electrochemically detected through the AuNP-catalysed oxidation of glucose at carbon fiber microelectrodes in alkaline solution, enabling the electrocatalytic detection of single AuNPs. This approach provides a basis for detecting and understanding the electrocatalytic properties of pristine nanoparticles in aqueous solutions. © 2017 Elsevier B.V.